Towards global action for appropriate technology - Bhalla, A. S. (Pergamon international library of science, technology, engineering, and social studies., 1979)
Towards Global Action for Appropriate Technology evaluates the feasibility of establishing and implementing an international mechanism for the promotion of appropriate technology. A strategy of reorienting research and development towards the rural and small-scale urban sectors is proposed, with emphasis on ultimately building national technological capacity in developing countries. This book is comprised of six chapters and begins with an overview of concepts, definitions, and strategies, followed by a discussion on some relatively unfamiliar criteria that should be taken into account in guid.